Pengaruh Model Pembelajaran Kooperatif Type PJBL Terhadap Hasil Belajar System Tata Udara Teknik Elektronika Siswa Kelas XI TE Di SMK N 3 Singaraja: The Influence of Project-Based Learning Model on Learning Outcomes of Air Conditioning Systems in Electronic Engineering Department at State Vocational School 3 Singaraja - Kadek Karuna Wibawa; Edi Elisa; I Nyoman Pasek Nugraha (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
The low learning outcomes of students in the Air Conditioning System course indicate the need for an instructional model that can enhance student engagement and improve the quality of the learning process. Project-Based Learning (PjBL) is an instructional model that is well suited to vocational education because it integrates conceptual understanding with practical experience through project completion. This study aimed to analyze the effect of implementing Project-Based Learning on the learning outcomes of eleventh-grade students in the Electronics Engineering Program at SMK Negeri 3 Singaraja. This study employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The study population consisted of 58 students, while the research sample comprised 29 eleventh-grade Electronics Engineering students. Data were collected using a multiple-choice objective test that had been validated through content validity assessment. The data were analyzed using descriptive statistics, normality and homogeneity tests, N-Gain analysis, and a paired-samples t-test with the assistance of SPSS software. The results showed that the mean learning outcome increased from 72.55 on the pretest to 82.00 on the posttest. The average N-Gain score was 0.7501, which falls into the high category, while the paired-samples t-test yielded a significance value of 0.001 (p < 0.05). These findings indicate that the implementation of Project-Based Learning has a positive and significant effect on students' learning outcomes in the Air Conditioning System course. Therefore, Project-Based Learning can be considered an effective instructional model for improving the quality of teaching and learning as well as students' competency achievement in technical and vocational education.